Socio-Cultural Impact in Tourism: A Case Study of Sauraha, Nepal - Poudel, Janardan (Journal of Advanced Academic Research, 2017)
Locaton: Sauraha is 166 km. south west from Kathmandu. It is situated at an altitude of 150m (492 feet) form the sea level. Its shape is rectangular and speared with east west direction. It is in close proximity with the Chitwan National Park, Tandi and Chitrasari being at a distance of 6 and 3 km. respectively from it. However, Tandi, the entry point to Sauraha, is situated on the east west highway, 20km. from the main city of Bharatpur. Objective: The objective of the study is to study the socio cultural impact in Tharus’ culture, customs, tradition and lifestyle by tourism. Methodology: Observation and questionnaire method will be used as data collection tools. This research will adopt descriptive research design. Descriptive in a sense: the research will carefully try to record all the observed events from the study area and describes fairly as possible. Result: Local people have changed their life style, their traditional values, cultural aspects and are following the borrowed values and aspects in the name of modernization. Conclusion: Sauraha, is the best location for the tourism industry. It is a part of Bachhauly VDC. It is worldwidely famous for its ethnic and cultural diversity. Numbers of tourists have come to visit the Chitwan National Park and most of the tourists go to Sauraha to stay and to study the cultural and traditional aspects of the Tharus. The cultural assimilation occurs when two cultures come in contact. The more technologically influential group gains supremacy while the latter society readily adopts the former’s way of living. The same phenomenon can be observed in Sauraha, where the host culture is highly influenced and affected by the guest culture.